2013
DOI: 10.1039/c3ra42629g
|View full text |Cite
|
Sign up to set email alerts
|

Photobactericidal polymers; the incorporation of crystal violet and nanogold into medical grade silicone

Abstract: Crystal violet and 2 nm gold nanoparticles were incorporated into medical grade silicone polymers by use of a novel two-step dipping strategy using water and water-acetone mixtures. Optical microscopic examination showed that the optimised polymer incorporated dye close to the polymer surface, with minimal dye encapsulation throughout the polymer bulk. The modified polymer was stable under aqueous conditions with negligible leaching of crystal violet from the polymer into surrounding aqueous solution at 37 uC.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
109
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 45 publications
(115 citation statements)
references
References 38 publications
3
109
1
Order By: Relevance
“…The significant photodynamic inactivation efficiencies of these PSs against the Gram-(+) Staphylococcus aureus (S. aureus, ATCC 6538), Gram-(-) Escherichia coli (E. coli, ATCC 25922), and drug resistant strain E. coli (CA-31) are studied. Methylene blue (MB), 25 …”
Section: ·-mentioning
confidence: 99%
“…The significant photodynamic inactivation efficiencies of these PSs against the Gram-(+) Staphylococcus aureus (S. aureus, ATCC 6538), Gram-(-) Escherichia coli (E. coli, ATCC 25922), and drug resistant strain E. coli (CA-31) are studied. Methylene blue (MB), 25 …”
Section: ·-mentioning
confidence: 99%
“…We have shown that the dyes can be readily impregnated into polymers using a swell-encapsulation-shrink process, and the polymers showed potent photobactericidal activity in white light 44,55 . In addition, incorporation of gold (Au) nanoparticles into a dye impregnated polymer significantly enhanced the photobactericidal effect 54,56 .…”
Section: Introductionmentioning
confidence: 99%
“…The development of light-activated antimicrobial surfaces such as crystal violet and nanogold incorporated silicone which kill S. epidermidis and E. coli by the action of light have been developed recently. 105 Likewise it was reported that light activation led to a decrease in S. aureus attachment among certain Ni-Ti alloy surface materials covered with titanium dioxide. 106 This was suggested to be due to the photon accumulation in the surface and likely increase in defects which could have resulted in free oxygen.…”
Section: Contact-active Materialsmentioning
confidence: 97%